Facile preparation of multifunctionalisable 'stealth' upconverting nanoparticles for biomedical applications12. Issue 26 (25th April 2018) - Nsubuga, Anne; Sgarzi, Massimo; Zarschler, Kristof; Kubeil, Manja; Hübner, René; Steudtner, Robin; Graham, Bim; Joshi, Tanmaya; Stephan, Holger
Abstract : Hide and Seek. Alendronate-modified upconverting nanoparticles display high colloidal stability, protein corona resistance, bright upconversion luminescence (800 nm excitation), and contain multifunctionalisation sites. Abstract : Pure hexagonal (β-phase) NaYF4 -based hydrophobic upconverting nanoparticles (UCNPs) were surface-modified with O -phospho-l -threonine (OPLT), alendronic acid, and PEG-phosphate ligands to generate water-dispersible UCNPs. Fourier-transform infrared (FTIR) spectroscopy was used to establish the presence of the ligands on the UCNP surface. These UCNPs exhibit great colloidal stability and a near-neutral surface at physiological pH, as confirmed by dynamic light scattering (DLS) and zeta potential ( ζ ) measurements, respectively. The particles also display excellent long-term stability, with no major adverse effect on the size of UCNPs when kept at pH 7.4. Upon exposure to human serum, PEG-phosphate- and alendronate-coated UCNPs showed no formation of biomolecular corona, as confirmed by SDS-PAGE analysis. The photophysical properties of water-dispersible UCNPs were investigated using steady-state as well as time-resolved luminescence spectroscopy, under excitation at ca. 800 nm. The results clearly show that the UCNPs demonstrate bright upconversion (UC) luminescence. Furthermore, the presence of reactive groups on the NPs, such as free amine groups in alendronate-coated UCNPs, enables further functionalisation of UCNPs with, for example, small molecules, peptides, proteins, and antibodies. Overall these protein corona resistant UCNPs show great biocompatibility and are worthy of further investigation as potential new biomaging probes.